Hegemonic masculinity as a predictor of body satisfaction - Verhagen, Megan (University of Wisconsin--Stout. Research Services, 2016)
The relationship between men and body satisfaction is a topic with increased traction within the academic community. However, there is currently no model in place that measures body satisfaction, and without a complete measure, it is difficult for researchers to understand what influences or predicts body satisfaction and how it influences men’s lives. This research used quantitative methods to investigate the use of hegemonic masculinity as a predictor for body satisfaction. A survey containing measures for hegemonic masculinity and body satisfaction was sent to self-identifying, college-aged men (N = 63) to measure the conformance to hegemonic masculinity and its relation to body satisfaction. Results indicate that hegemonic masculinity, as it is currently measured, is not a predictor for body satisfaction. These results suggest that either the production of hegemonic masculinity has changed since measures were last produced or that hegemonic masculinity is not the production of masculinity that interacts with body image. The author discusses why an understanding of the predictors for body satisfaction in men is important and suggests what research can be produced in the future to eventually create a model that can accurately measure body satisfaction and influence the establishment of systems that decrease risk taking in men who experience body dissatisfaction.
Research article with graphs and tables.
Keywords: body satisfaction; risk behaviors; hegemonic masculinity; Body image; Body image in men; Masculinity